Variational 3D mesh segmentation - Zhang, Juyong (2012)
3D Mesh segmentation refers to the process of extracting subparts or components from an existing mesh or decomposing a mesh model into multiple meaningful components. Mesh segmentation is of great practical importance in many mesh related processing and applications. The challenge with 3D mesh segmentation lies in the fact that the segmentation algorithm is expected to extract meaningful components or decompose a mesh into meaningful parts which are consistent with user intention, geometric mesh attributes and human shape perception. The thesis has made several contributions to address the challenge in 3D mesh segmentation.